2017
DOI: 10.4103/ejd.ejd_56_17
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomographic evaluation of styloid process: A retrospective study of 1000 patients

Abstract: Objective:The styloid process (SP) is a bony projection, located just anterior to the stylomastoid foramen, the normal length of which is approximately 20–30 mm. The length of SP when exceeds 30 mm it is said to “elongated.” The purpose of this retrospective study was to assess the prevalence of elongated SP (ESP) by cone beam computed tomography (CBCT) examination in Turkish subpopulation and its relation to gender and age.Materials and Methods:This study analyzed CBCT of 1000 patients who were randomly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
2
14
0
1
Order By: Relevance
“…Cone beam computed tomography can be used as an advanced diagnostic tool to assess the SP pattern, Buyuk et al [4], Donmez et al [7], and Öztunç et al, [21] used it on Turkish population, Kailasam et al [14], and Ramadoss et al [27], on Indian population, Khairallah A [15], used it on Lebanese population, Andrei et al [2] used it on Romanian population, Czajka et al [6] used it in polish cases.…”
Section: Discussionmentioning
confidence: 99%
“…Cone beam computed tomography can be used as an advanced diagnostic tool to assess the SP pattern, Buyuk et al [4], Donmez et al [7], and Öztunç et al, [21] used it on Turkish population, Kailasam et al [14], and Ramadoss et al [27], on Indian population, Khairallah A [15], used it on Lebanese population, Andrei et al [2] used it on Romanian population, Czajka et al [6] used it in polish cases.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic assessment including panoramic radiographs and computed tomography (CT) scan presents useful information to diagnose ES [ 1 , 16 , 22 ]. CT has been recommended as the best imagery to evaluate the position, length, width, and angulation of the SPs, as well as their proximity to adjacent neuro-vascular structures [ 13 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elongation of the SP classically occurs after a traumatic event such as the fracture of the SP, a minor trauma of the neck, or after tonsillectomy [ 1 , 2 ]. The incidence of elongated SP is thought to be between 4% and 15% of the population [ 3 , 13 , 14 ]. However, a minority of patients with elongated SP are symptomatic [ 3 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Authors even concluded CBCT as one of the alternative to other imaging modalities in the assessment of the styloid processes. 29,30 Till our knowledge, this is first study conducted on Rajasthan population evaluating the styloid processes prevalence. In the present study, 854 (22.47%) radiographs showed elongated styloid processes.…”
Section: Discussionmentioning
confidence: 99%